Impact of the 2007/2008 global financial crisis on the stock market in Nigeria - Peter Njiforti (CBN Journal of Applied Statistics, 2015)
The convergence of global economy makes all countries and all markets sensible to the happenings in other countries (the contagious effect). The 2008 global financial crisis that had its origin from USA was alleged to have had varying degree of impacts on different capital markets in various countries. This paper investigated the impact of the 2007/2008 global financial crisis on the Nigerian capital market. Monthly time series data from January 2006 to December 2009. All Share Index (ASI) was used as proxy for the performance of the Nigerian Capital market, while Credit to the Private Sector (CPS), Price of Crude Oil (POIL), Money Supply (MS) and Dow Jonews Industrial Average (DJIA) were the set of explanatory variables used to ascertain the effects of the crisis on the capital market in Nigeria. The paper employed the Vector Error Correction (VEC)model for the analysis. Based on the estimated Cointegration and the VEC analyses, the paper found that the global finanancial crisis adverstly and significantly affected the Nigerian capital market both in the shortrun and long run. This was clearly evidenced by the fact that POIL slumped to a record low level, MS equally decreased and the CPS contracted thereby reducing the idle balances which could have been invested in stocks. All these are clear evidences of the crisis on the performance of the Nigerian capital market. Hence the global financial crisis of 2007/2008 was no respecter of any economy, eventhough some writers in Nigeria were quick in concluding that the Nigerian financial sector was insulated and robust, but it was not long after the economy was brought to its knees as the stock market in Nigeria crashed leading to a valuable lost of capital assets and investments.
Keywords: C22; Q02; 330; Global financial crisi; Nigeria stock Maket; U.S. Stock Market